2022
DOI: 10.1088/1748-9326/ac9325
|View full text |Cite
|
Sign up to set email alerts
|

Exploring green gentrification in 28 global North cities: the role of urban parks and other types of greenspaces

Abstract: Introduction: Although cities globally are increasingly mobilizing re-naturing projects to address diverse urban socio-environmental and health challenges, there is mounting evidence that these interventions may also be linked to the phenomenon known as green gentrification. However, to date the empirical evidence on the relationship between greenspaces and gentrification regarding associations with different greenspace types remains scarce. Methods: This study focused on 28 mid-sized cities in North America a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 58 publications
(55 reference statements)
0
8
0
Order By: Relevance
“…Despite this observed relationship, low-income, minoritized, and socially marginalized communities often have far less access to this low-cost health intervention 9,10. Furthermore, greenspace development in these priority areas can often lead to gentrification, meaning low-income, minoritized, and socially marginalized people continue to have less access to greenspaces 13,14…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this observed relationship, low-income, minoritized, and socially marginalized communities often have far less access to this low-cost health intervention 9,10. Furthermore, greenspace development in these priority areas can often lead to gentrification, meaning low-income, minoritized, and socially marginalized people continue to have less access to greenspaces 13,14…”
mentioning
confidence: 99%
“…9,10 Furthermore, greenspace development in these priority areas can often lead to gentrification, meaning low-income, minoritized, and socially marginalized people continue to have less access to greenspaces. 13,14 Four main pathways have been identified through which greenspace benefits mental health: stress reduction, social cohesion, pollution reduction, and outdoor recreation. 15,16 Stress reduction occurs because of the restorative properties of nature, such as breathing fresh air or intentionally taking time to relax, which may be achieved in public and private greenspaces.…”
mentioning
confidence: 99%
“…Studies have shown greenspace development is not equitable; such that primarily white and primarily high income communities (Mears & Brindley, 2019 ) and cities (Rigolon et al., 2018 ) often have the best access to ample, high quality greenspaces. In the past, greenspace developments in minority neighborhoods have often led to gentrification (Kim & Wu, 2022 ; Triguero‐Mas et al., 2022 ); with the most affluent benefiting from increased greenspaces; while minority residents and low‐income residents face social exclusion and rising housing costs (Cole et al., 2019 ). Future greenspace interventions need to ensure the development of greenspaces that serve all community members, without leading to displacement and gentrification.…”
Section: Discussionmentioning
confidence: 99%
“…Research indicates that greenspace development is not equitable; with primarily white and primarily high income communities 68 and cities 69 often seeing the greatest quantity, accessibility and/or quality of public greenspaces. Historically, development of greenspaces in minority neighborhoods has often led to gentri cation 70,71 . Furthermore, some research cautions that in gentrifying neighborhoods, greenspace bene ts the most a uent and may result in social exclusion for low-income and minority residents 72 .…”
Section: Discussionmentioning
confidence: 99%